The urgency of establishing a public service agency for tourism management in Gunungkidul region - Rahmawati, Anisa; Al Hazmi, Raldin Alif (Jurnalku, 2024)
Gunungkidul has great tourism potential, especially in coastal areas, but its management is still not optimal. As a result, the economic benefits that should be achieved from the tourism sector have not been fully realised. This research aims to analyse the current condition of tourism in Gunungkidul and assess the urgency of establishing a Public Service Agency (BLU)-based Authority Agency in the region. The method used in this research is a descriptive qualitative approach, with the main focus on the importance of establishing a BLU-based Authority Agency in Gunungkidul. The research findings show that, although Gunungkidul has many attractive tourist destinations, the existing potential has not been fully utilised. In addition, the regional economy is still highly dependent on traditional sectors, with tourism contributing insignificantly. The establishment of a BLU-based Authority Agency is considered a strategic step to optimise tourism management in Gunungkidul. This agency is expected to play a role in coordinating, synchronising, and facilitating the planning, development, and control of tourism areas, so that tourism potential can be optimised to encourage regional economic growth.